2018
DOI: 10.3389/fmicb.2018.03006
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Escherichia coli Using Nanosecond Electric Fields and Nisin Nanoparticles: A Kinetics Study

Abstract: Nisin is a recognized bacteriocin widely used in food processing, however, being ineffective against gram-negative bacteria and in complex food systems. As a result, the research of methods that have cell wall–permeabilizing activity is required. In this study, electroporation to trigger sensitization of gram-negative bacteria to nisin-loaded pectin nanoparticles was used. As a model microorganism, bioluminescent strain of E. coli was introduced. Inactivation kinetics using nanosecond pulsed electric fields (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 52 publications
(60 reference statements)
0
7
0
Order By: Relevance
“…For use in food industry, the range of permissible antibacterials is limited to those that either occur naturally in foods or are approved as food additives, but if superior potentiation by electroporation for substances targeting the bacterial cell wall holds generally true for antibacterials, applications for food and beverage preservation can (re)focus on those among the permissible substances that target the wall. Currently, one such substance widely recognized as targeting the wall is nisin ( Malanovic and Lohner, 2016 ; Modugno et al, 2018 ), and there is at least one report of its potentiation by electroporation, achieving moderate (∼2–3 log) inactivation rates against E. coli ( Novickij et al, 2018b ). However, at least one study found no potentiating effect of electroporation for nisin against either E. coli or Salmonella typhimurium ( Saldaña et al, 2012 ), while the efficacy of nisin alone is largely limited to Gram-positive bacteria ( Asaduzzaman and Sonomoto, 2009 ) and can only be extended to Gram-negative bacteria by artificially modifying the nisin molecule ( Field et al, 2015 ; Zhou et al, 2016 ) or by binding nanocomposites to it ( Vukomanović et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…For use in food industry, the range of permissible antibacterials is limited to those that either occur naturally in foods or are approved as food additives, but if superior potentiation by electroporation for substances targeting the bacterial cell wall holds generally true for antibacterials, applications for food and beverage preservation can (re)focus on those among the permissible substances that target the wall. Currently, one such substance widely recognized as targeting the wall is nisin ( Malanovic and Lohner, 2016 ; Modugno et al, 2018 ), and there is at least one report of its potentiation by electroporation, achieving moderate (∼2–3 log) inactivation rates against E. coli ( Novickij et al, 2018b ). However, at least one study found no potentiating effect of electroporation for nisin against either E. coli or Salmonella typhimurium ( Saldaña et al, 2012 ), while the efficacy of nisin alone is largely limited to Gram-positive bacteria ( Asaduzzaman and Sonomoto, 2009 ) and can only be extended to Gram-negative bacteria by artificially modifying the nisin molecule ( Field et al, 2015 ; Zhou et al, 2016 ) or by binding nanocomposites to it ( Vukomanović et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study we show in vitro results for the efficacy of 600-ns PEF to inactivate Escherichia coli and Lactobacillus acidophilus. While the effects of nsPEF have been studied on E. coli (Chalise et al 2006;Perni et al 2007;Guionet et al 2014Guionet et al , 2015Novickij et al 2018) and other species such as Staphylococcus aureus (Chaturongakul and Kirawanich 2012; Vadlamani et al 2018;Novickij et al 2019), Salmonella typhimurium (Perni et al 2007) and Bacillus subtilis (Katsuki et al 2002); we chose to compare the effects of E. coli with L. acidophilus for two reasons. First, several studies have suggested that cell size and shape play a critical role in transmembrane potential charging and subsequent membrane pore formation (Kandušer and Miklavčič 2008;Khan and El-Hag 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, nisin is ineffective against Gram-negative bacteria due to the impermeability of their outer membrane [ 12 ]. Gram-negative bacteria may be inactivated by the use of nisin in combination with physical methods, such as high hydrostatic pressure or pulsed electric fields, which induce the permeabilization of their outer membrane [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%